Seeking a way in/resisting a way out: labor market dualization and democratic transition in Serbia and Tunisia - Rennick, Sarah Anne; Žilović, Marko (Frontiers in Political Science, 2025)
Studies investigating the political relevance of labor market dualization have gathered compelling evidence that labor market status shapes workers’ political preferences and their modes of participation, shedding significant light on shifts in partisan politics and socio-economic policies, as well as broader transformations to political systems. Yet, the study of labor market dualization in contexts of democratic transitions, and their role in shaping transitional processes, has been largely uninvestigated. In particular, two fundamental questions, lying at the nexus of labor market segmentation theory and democratic transition theory, remain unanswered: how does the context of democratic transition inform political participation of labor market insiders and outsiders, and what is the impact of their mobilization on transition processes? To answer these questions, the paper considers two instances of dualized labor market mobilization under democratic transition: the Union of Unemployed Graduates in Tunisia during the period 2011–2014, and industrial workers in Serbia in the early 2000s, who were under severe threat to lose their insider status with the shift to a liberalized economy. Drawing on Della Porta et al.’s (2016) theorization of the interactionist and relational dimensions of social movement action, democratization, and revolution, we posit that democratizing regimes are able to exploit demands for labor market insider status to stabilize transition processes. The paper finds that, despite many contextual differences between the two cases, the politics of labor market inclusion and exclusion displayed remarkable similarities. First, both cases show how organized actors in the field of labor contestation were channeled into modes of participation that acquiesced to the technocratic and procedural logic of the transition. Second, in both cases, contestation against the democratic transition’s political economy and its impact on labor market outsiders/future outsiders was able to be assuaged not through systemic change but rather through a strategy of fragmentation and limited concessions. As an implication, we find that while these strategies proved effective at reducing street level contestation they may have also reduced workers’ substantive evaluation of democratic transition, which in turn left Serbia’s and Tunisia’s democracies more vulnerable to the threat of future reversals by populist leaders.